The Role Of The Fogg Behavioural Model In Bridging The Gap Between Intention And Behaviour In The Sustainable Consumption Of Bottled Water In Indonesia - Maria Ramanyani; Willy Arafah; Robert Kristaung (International Journal Of Humanities Education and Social Sciences (IJHESS), 2025)
This research aims to analyse the role of the Fogg Behaviour Model in bridging the gap between purchase intention and behaviour on sustainable consumption of bottled drinking water. The research design/plan used is based on hypothesis testing. This research is quantitative and non-experimental. It is based on a questionnaire sent to 228 respondents. The survey was conducted in July 2024, and respondents were consumers of bottled water. Using SPSS and SmartPLS to process and analyse data. The results of the research show that there is a positive and significant influence of green purchase intention on motivation, ability and urge to buy bottled drinking water. Motivation, ability and prompting have been shown to act as a complete mediator to close the gap between green purchase intention and green purchase behaviour. The mediating effects of motivation, ability and prompting can lead to a stronger green purchasing behaviour. There are limitations to this research, including the fact that it is quantitative and conducted over a relatively short period of time, and that it only looks at sustainable purchasing behaviour for bottled water, which is relatively affordable.